The Competencies Leaders Have to Have for Innovation: A Qualitative Research from Colombia - Jesús Enrique BELTRAN VIRGUEZ; Mariana PALLARES AVENDAÑO (Communications of International Proceedings, 2024)
The present study adopts a hermeneutic approach to explore the competencies required for innovation and provides a qualitative descriptive view of business and innovative practices, based on the participation of 118 executives from various companies and sectors in Colombia. The research addresses a current need within the field of study due to the lack of information and studies associated with managerial practices, innovation capabilities, and overall organizational reality and innovative performance. To the extent that there is insufficient empirical evidence to address this important topic. Research with Colombian executives from diverse companies reveals a discrepancy between perception and effective implementation of innovation within organizations. While the majority of executives express confidence in their ability to innovate, operational demands and time constraints hinder these efforts. Additionally, many lack clarity on how to carry out innovation and show limited engagement in external relationships for open innovation. There is a recognized need to enhance managerial education in innovation and establish stronger connections with external entities. The research also underscores the importance of better understanding companies' innovation capabilities and managerial competencies, along with conducting further research in this area. Recommendations include strengthening managerial education in innovation, fostering external relationships for open innovation, and creating conducive environments for innovation within organizations. Finally, theoretical developments are contrasted with business reality, and recommendations are provided for enhancing business schools.